Cannabinoids as Key Regulators of Inflammasome Signaling: A Current Perspective - Suryavanshi, Santosh V.; Kovalchuk, Igor; Kovalchuk, Olga (Frontiers in Immunology, 2021)
Inflammasomes are cytoplasmic inflammatory signalling protein complexes that detect microbial materials, sterile inflammatory insults, and certain host-derived elements. Inflammasomes, once activated, promote caspase-1-mediated maturation and secretion of pro-inflammatory cytokines, interleukin (IL)-1β and IL-18, leading to pyroptosis. Current advances in inflammasome research support their involvement in the development of chronic inflammatory disorders in contrast to their role in regulating innate immunity. Cannabis (marijuana) is a natural product obtained from the Cannabis sativa plant, and pharmacologically active ingredients of the plant are referred to as cannabinoids. Cannabinoids and cannabis extracts have recently emerged as promising novel drugs for chronic medical conditions. Growing evidence indicates the potent anti-inflammatory potential of cannabinoids, especially Δ9-tetrahydrocannabinol (Δ9-THC), cannabidiol (CBD), and synthetic cannabinoids; however, the mechanisms remain unclear. Several attempts have been made to decipher the role of cannabinoids in modulating inflammasome signalling in the etiology of chronic inflammatory diseases. In this review, we discuss recently published evidence on the effect of cannabinoids on inflammasome signalling. We also discuss the contribution of various cannabinoids in human diseases concerning inflammasome regulation. Lastly, in the milieu of coronavirus disease-2019 (COVID-19) pandemic, we confer available evidence linking inflammasome activation to the pathophysiology of COVID-19 suggesting overall, the importance of cannabinoids as possible drugs to target inflammasome activation in or to support the treatment of variety of human disorders including COVID-19.